226k views
4 votes
Use substitution to solve each system of equations. y = 4x + 22 4x – 6y = –32

(–5, 2)

(2, –5)

(–8, 1)

(4, 7)

1 Answer

4 votes

Answer:

(-5,2)

Explanation:

The given system is

1st equation: y = 4x + 22

2nd equation: 4x – 6y = –32

We plug in the first equation into the second equation to obtain:

4x – 6(4x + 22) = –32

We expand the parenthesis to obtain:

4x – 24x -132= –32

Group similar terms;

4x – 24x = –32+132

Combine similar terms

-20x =100

Divide both sides by -20

x =-5

Put x=-5 into the 1st equation

y = 4(-5) + 22

y=-20+22

y=2

The solution is:

(-5,2)

User Brent Traut
by
5.7k points